Fighting COVID-19 in Nigeria Leadership and collaboration in Numbers 12:9–16 - Uroko, Favour C.; Nwaoga, Chinyere T. (2021)
Numbers 12:9-16 deals with a situation that deserves an urgent response. It defines leadership and collaboration in the period of crisis. The pericope provides roadmaps on how Nigerians can tackle the contemporary coronavirus disease 2019 (COVID-19) pandemic in Nigeria. Miriam was struck with an incurable illness from God. Moses, with his leadership skills, was able to consult God, who insisted that Miriam be isolated and quarantined for seven days to prevent an escalation of the infectious disease. Using the narrative analysis, the study demonstrates that Moses’ display of transparent and systematic profiling, effective leadership and collaboration of all Israelites helped to curb the pandemic from escalating. Having observed this phenomenon, the researcher believes that the pericope will speak anew to the current fight against the coronavirus pandemic in Nigeria. Findings reveal that infective leadership and collaboration led to increased poverty, insecurity and domestic abuse in Nigeria during the coronavirus era.Intradisciplinary and/or interdisciplinary implications: The research is based on the rising cases of the coronavirus in Nigeria. It was discovered that a lack of transparency, a lack of leadership, and civil disobedience are the major factors causing a failure in the fight against the COVID-19 pandemic in Nigeria. Disciplines implicated include Sociology, Old Testament and Dogmatics.
Keywords: Bibel Numeri 12,9-16; Covid-19; Numbers 12:9–16; Coronavirus; Isolation; Lockdown; Quarantine; Bibel Numeri 12,9-16